The relationship between Gamification and Socioemotional Skills in educational praxis - Morales-Escareño, Claudia Alejandra; Vences Esparza, Angélica; Flores-Alanís, Irma María; Hernández Cueto, Jaquelina Lizet (Opción, 2022)
The constant scientific search for innovative pedagogical practices by teachers indicates the reality of informants in virtual and face-to-face contexts under challenging educational schemes. The research aims to understand the relationship between Gamification and Socioemotional skills developed in the classroom by teachers, through the quantitative paradigm. Cronbach’s Alpha supports the reliability of the instrument with the significant sample of 941 teachers studied in Coahuila, through central tendency statistics and dispersion coefficients, which corroborate the connection of the two Axes.